Strategi Pemasaran Produk Kerajinan Eceng Gondok Di Desa Banyu Hirang Kecamatan Amuntai Selatan Kabupaten Hulu Sungai Utara (Studi Kasus Kelompok Usaha Bersama (KUB) “ Kembang Ilung”) - Yani Warliyanti (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2012)
This study aims (i) to know the strength, weaknesses, threats and opportunities, and (ii) to find out how the marketing strategy of the